HOMICIDE IN SIDNEY SHELDON’S TELL ME YOUR DREAMS - Seffi Rahmawati; Vita Vedityaningtyas (Universitas PGRI Madiun, 2017)
Multiple Personality Disorder is reflected in the novel entitled Tell Me Your Dreams. It is through the character, Ashley Patterson that commits the homicide to five men. The analysis focuses on (1) describing the symptoms of Multiple Personality Disorder in Ashley Patterson; and (2) describing the effect of Ashley’s Multiple Personality Disorder to the homicide. This research uses psychological approach. The research uses the qualitative research and documentation. The source of data is from Sidney Sheldon’s novel Tell Me Your Dreams as the primary data. The supporting data are from journal articles, books, website articles, etc. related to psychology and personality. The theory applies the Multiple Personality Disorder and homicide. The result of the research reveals that (1) first, Ashley always feel annoyed by the recurrent traumatic even in her life and by the terrible nightmare. Second, Ashley, or Toni, always tries to avoid the feeling about the trauma and tries to avoid the activities or situation related to the traumatic events. Third, Ashley suffered the amnesia or inability to recall the important aspect in her traumatic memories. Additionally, the specific symptoms are seen from her different languages and speech accents; the change in her facial expression which indicate the switching process; and her different handwriting style. (2) The effect of Ashley’s Multiple Personality Disorder create defenses, which lead her to take the impulsive action, and the worst thing is that she can kill people.